Evaluasi Implementasi Putusan Mahkamah Konstitusi Terhadap Desain Surat Suara Calon Tunggal Dalam Pilkada - Oktavia, Enika Maya; Syafei, Rizki Maulana; Fatna, Tsalis Khoirul (Jurnal Hukum & Pembangunan, 2025)
The phenomenon of single candidates in regional elections in Indonesia has created a dilemma in applying democratic principles, especially regarding ballot design that often confuses voters. The Constitutional Court’s Decision Number 100/PUU-XIII/2015 mandated a plebiscite design with “agree” or “disagree” options for single candidates. However, in practice, this design has been distorted with the presence of a blank box without adequate explanation. This study aims to evaluate the extent to which the discrepancy between the Constitutional Court's decision and actual ballot design practices affects voter understanding and the quality of democracy. This study employs a normative juridical method with a qualitative-descriptive approach, relying on literature reviews and secondary data analysis from legal documents and news reports. The theoretical framework uses the "ambiguity effect" and "picture superiority effect," explaining how visual ballot design can influence voter preferences cognitively. The study analyzes variables of compliance with the Constitutional Court's decision and voter understanding as parameters. Data collection procedures are conducted through a literature review. The results indicate that the inconsistency of ballot design with the Court’s decision leads to voter confusion, where the ambiguity of the blank box often directs voters toward choices that may not reflect their true preferences. This highlights the need for policy revisions to better align with democratic principles and support voter decision-making quality in regional elections in Indonesia. Keywords: Single Candidate, Regional Elections, Ballot Design, Blank Vote, Simultaneous Election